La division sexuelle du travail militant dans les assemblées générales : le cas des mouvements de « sans » - Xavier Dunezat (Amnis)
According to the author, the gender of militancy can be revealed in questionning the sexual division within militant tasks which are done in the “outsiders” or “without” social movements. This analysis leans on participating observations during unemployed mobilizations in 1998 (in Rennes and in Morlaix in Brittany) and illegal immigrant's mobilizations in the 2000s. The quantitative and qualitative analysis of the militant tasks within militant meetings show different level of participation, in function of the sexual groups. The practices, prescribed in general assembly, are mainly the fact of male militant, but the consideration of the « incidents » and the not prescribed practices widens the real militant work: feminine militant practices are in contradiction with the vision of a more passive feminine commitment. The social heterogeneousness (at the level of « militant capital », class or race…) within every sexual group must be integrated into the analysis to read the gender of social movements.